Automated hexahedral meshing of knee cartilage structures – application to data from the osteoarthritis initiative. Issue 14 (26th October 2017) - Rodriguez-Vila, B.; Sánchez-González, P.; Oropesa, I.; Gomez, E. J.; Pierce, D. M.
Abstract: We propose a fully automated methodology for hexahedral meshing of patient-specific structures of the human knee obtained from magnetic resonance images, i.e. femoral/tibial cartilages and menisci. We select eight patients from the Osteoarthritis Initiative and validate our methodology using MATLAB on a laptop computer. We obtain the patient-specific meshes in an average of three minutes, while faithfully representing the geometries with well-shaped elements. We hope to provide a fundamentally different means to test hypotheses on the mechanisms of disease progression by integrating our patient-specific FE meshes with data from individual patients. Download both our meshes and software athttp://im.engr.uconn.edu/downloads.php .